Effects of nutrition and soil water availability on water use in a Norway spruce stand - Phillips, Nathan; Bergh, Johan; Oren, Ram; Linder, Sune (Tree Physiology, 2001)
We investigated effects of nutrition and soil water availability on sap flux density, transpiration per unit leaf area ( E L ), and canopy stomatal conductance ( G S ) of Norway spruce ( Picea abies L. (Karst.)) in northern Sweden during the 1996 growing season. Our objectives were to determine (1) if artificially imposed drought (65% rain diversion) reduces soil water sufficiently to cause physiological limitations to whole-tree and plot-scale water transport, and (2) whether increased capacity for water transport resulting from fertilization-induced increases in leaf (> 3-fold) and sapwood areas (> 2.3-fold) deplete soil water sufficiently to cause a negative feedback on G S and E L . We monitored soil water content (θ) and soil water potential (Ψ S ) in control (C), drought (D), fertilized (F) and irrigated + fertilized (IL) treatment plots, along with site meteorological conditions. Ten trees per plot were monitored for sap flow. Although there were significant treatment differences in mean daily E L (C > D > F; P < 0.01) and G S (C > D > F; P < 0.05), variation in absolute magnitudes was small. Therefore, transpiration differences on a unit ground area basis ( E C ) were nearly proportional to leaf area differences. Precipitation was well distributed throughout the study period and so Ψ S remained high, except during short dry periods in Plot F when it declined rapidly. Thus, although soil water was not limiting to G S , E L or E C when precipitation was uniformly distributed throughout the growing season, we cannot conclude that water availability would not limit G S in fertilized stands if the seasonal distribution of precipitation were altered.